1995
DOI: 10.1180/minmag.1995.059.397.12
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hausmannite from hydrothermally altered manganese ore in the Palaeoproterozoic Kalahari manganese deposit, Transvaal Supergroup, South Africa

Abstract: Hausmannite (Mn304), a manganese oxide with a tetragonally distorted spinel structure, is considered to be ferrimagnetic with a very low Curie temperature of 42.5 K. However, strongly magnetic hausmannite has been discovered in some of the hydrothermally altered high-grade manganese ores of the giant Kalahari manganese deposit in South Africa. EDS-electron microprobe analyses indicate magnetic hausmannite to contain on average between 3 and 11.3 wt.% Fe203. In contrast non-magnetic hausmannite contains on aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Substitution of Mn 3+ (0.645 Å, HS) by Fe 3+ (0.645 Å, HS) cations results in minor, but measurable changes in unit-cell parameters, and a decrease of Jahn-Teller distortion with increasing Fe 3+ concentrations [14]. Neutron diffraction results at 10 K from Baron et al [14] indicate that Fe-rich hausmannite is not the source for high-temperature (Curie temperature of 750 K) ferrimagnetism in hausmannite-rich ores from the KMF that was described by Gutzmer et al [13]. The authors indicated that minor amounts of Mn-bearing hematite in the hausmannite-rich ores may be the source for the unusual magnetic properties, but this was not confirmed.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Substitution of Mn 3+ (0.645 Å, HS) by Fe 3+ (0.645 Å, HS) cations results in minor, but measurable changes in unit-cell parameters, and a decrease of Jahn-Teller distortion with increasing Fe 3+ concentrations [14]. Neutron diffraction results at 10 K from Baron et al [14] indicate that Fe-rich hausmannite is not the source for high-temperature (Curie temperature of 750 K) ferrimagnetism in hausmannite-rich ores from the KMF that was described by Gutzmer et al [13]. The authors indicated that minor amounts of Mn-bearing hematite in the hausmannite-rich ores may be the source for the unusual magnetic properties, but this was not confirmed.…”
Section: Introductionmentioning
confidence: 90%
“…utzmer et al [13] reported both magnetic and non-magnetic hausmannite samples ari manganese field (KMF; samples-2 and -3 in Table 1). It seems that substitution of Gutzmer et al [13] reported both magnetic and non-magnetic hausmannite samples from Kalahari manganese field (KMF; samples-2 and -3 in Table 1). It seems that substitution of Fe 3+ cations at the M site give rise to a magnetic sample.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fukuoka 1983). The Fe,Mn-oxides are known to carry magnetic remanence (e.g., Gutzmer et al 1995;Baron et al 1998), although the magnetic properties (Curie temperature, saturation magnetization, saturation remanence, coercive force) of iwakiite are only poorly known. Matsubara et al (1979, p. 386) state simply: It [iwakiite] is more strongly magnetic than ordinary jacobsite by a simple hand magnet examination.…”
Section: Magnetic Properties Of Columbite-tantalite-ixiolite Samplesmentioning
confidence: 99%